KEPASTIAN HUKUM BERALIHNYA BENDA JAMINAN FIDUSIA KARENA PUTUSAN HAKIM (Studi Kasus PT. Bii Finance Center) - Susanto . (Jurnal Surya Kencana Dua : Dinamika Masalah Hukum dan Keadilan, 2016)
Legal certainty can be realized through good and clear in a law and its application will also clear. Legal certainty is also required in fiduciary. Act No. 42 of 1999 on Fiduciary is one of them as a guideline for transfer of fiduciary security object. Abdul Rozak initially accept objects of Wiliam Herudinata fiduciary underhand manner in which the recipient of fiduciary security object is PT. BII Finance Center. As a good faith Abdul Rozak convey to PT. BII Finance Center in writing about the transition under the arm, but the PT. BII Finance Center did not respond nor reject the installments paid by Abdul Rozak, on the other hand Wiliam Herudinata unknown. When installment was paid by PT. BII Finance refused to surrender fiduciary objects to Abdul Rozak. The top permasalahn Abdul Rozak filed suit in the District Court of Tangerang to register case number: 412 / Pdt.G / 2015 / PN.TNG. Judges on the lawsuit tersebuat the case in favor of Abdul Rozak with one of the legal considerations that Abdul Rozak have good faith and PT. BII Finan Center does not reject or endorse the transitional credit agreement with the fiduciary guarantee, it shall be rendered by the judges that Abdul Rozak is the only party entitled to take that object of the fiduciary guarantee.Keywords: Rule of Law, Fiduciary, Judicial Power